Optical and morphological evolution of black TiOx synthesized in water by Nd:YAG laser. Issue 9 (27th July 2017) - Spucches, D.; Zimbone, M.; Cacciato, G.; Ruffino, F.; Privitera, V.; Grimaldi, M. G.
Abstract : Optical and morphological properties of nanostructured TiO x film formed by 532 nm nanosecond pulsed laser irradiation in water is analysed. We observe three different surface features: blackening, surface pits and sub‐surface bubbles. The appearance of these features is allowed once an irradiation fluence of 0.9 J cm −2 is used. Nevertheless, blackening, formation of pits and bubble are delayed until an accumulated fluence threshold of 7.5, 23 and 24 J cm −2 is achieved respectively. A fully evolved complex nano‐porous structure is obtained at an accumulated fluence of 100 J cm −2 . A possible mechanism of formation of these features was inferred.